The roles of conceptual modelling in improving construction simulation studies: A comprehensive review. (October 2020) - Abdelmegid, M.A.; González, V.A.; O'Sullivan, M.; Walker, C.G.; Poshdar, M.; Ying, F.
Abstract: The conceptual modelling phase of simulation studies has proven to be effective in enhancing the impact of simulation modelling in different domains. However, this simulation phase did not receive much attention in the construction simulation domain. The objective of this paper is to identify the roles that conceptual modelling can play in advancing the engagement, accuracy, and adoption (among other things) of discrete-event simulation studies in construction. In this paper, a Systematic Literature Review (SLR) is conducted, which involves a comprehensive search of databases and researchers' profiles to identify journal papers, conference articles, books, and theses that have reported the benefits of conceptual modelling for discrete-event simulation studies. The review resulted in 82 documents that were published from 2000 to 2020. Results indicate that the benefits of conceptual modelling include facilitating communications between stakeholders, capturing sufficient information for the simulation model, improving the quality of simulation models, guiding other simulation modelling activities, and facilitating verification and validation of simulation models. By linking these benefits to the current research agenda in construction simulation, this paper shows the significance and potential of the conceptual modelling phase to enhance the impact of discrete-event simulation studies in construction.